Legal Protection For Children Who Are Victims of Sexual Violence So That Causes Mental Illness Disorders - Berliana Maya Agustina Manullang; Kartina Pakpahan; Immanuel Simanjuntak (Fakultas Syariah INSURI Ponorogo, 2026)
This research analyzes the legal protection provided to child victims of sexual violence who suffer from mental illness disorders, specifically examining Court Decision Number 2836/Pid.Sus/2022/PN.Mdn. Using a normative juridical method with statutory and case approaches, this study identifies that sexual violence against children results in profound psychological consequences, including trauma, depression, anxiety, and severe disorders such as PTSD, bipolar disorder, and schizophrenia. Although Indonesia has established a legal framework through the Child Protection Law and the Witness and Victim Protection Law to mandate rehabilitation and psychological support, its practical application often remains perpetrator-focused, leaving significant gaps in the victim's long-term mental recovery. In the analyzed case, the judge's considerations integrated the victim's severe mental state—characterized by self-harm and the need for intensive medical treatment—as a basis for sentencing. The study concludes that optimal legal protection requires a shift toward a victim-centered approach, necessitating stronger collaboration among law enforcement, healthcare providers, and the government to ensure comprehensive rehabilitation and the fulfillment of victims' rights.